Seasonal distribution and evolving forms of multiple sclerosis patients diagnosed from April 2004 to November 2007 Distribución estacional y formas evolutivas de esclerosis múltiple en pacientes diagnosticados entre Abril del 2004 y Noviembre del 2007 - Hermes Fundora-Hernández; Alberto J. Dorta-Contreras; Maray Socias-López; Silvana Fraga-Santana; Silvia Nicté Villatoro-Rodríguez; Bárbara Padilla-Docal; Elena Noris-García; Raisa Bu-Coifiu-Fanego; Marlén González-Hernández (Arquivos de Neuro-Psiquiatria)
BACKGROUND: Multiple sclerosis (MS) was first reported in Cuba in 1965. The most frequent appearance is observed in the first six months of the year. OBJECTIVE: To determine the seasonal distribution and evolving forms of MS patients diagnosed with the disease between April 2004 and November 2007. METHOD: Twenty-one patients with suspected MS and 42 outbreaks were studied. Patients were classified according to Lublin and Revingold's criteria for clinical forms and according to McDonald. RESULTS: Most patients were classified in outbreak and remission and only two patients classified as primary-progressive multiple sclerosis. The higher number of outbreaks occurred in the first two quarters of the year. CONCLUSION: It is recommended to study further weather variables that may be related to the emergence of these outbreaks in our environment. INTRODUCCIÓN: La esclerosis múltiple (EM) fue reportada en Cuba por primera vez en 1965. Se ha venido observando la aparición más frecuente en los primeros seis meses del año. OBJETIVO: Determinar la distribución estacional y formas evolutivas de EM en pacientes con diagnóstico de esta enfermedad entre abril 2004 y noviembre 2007. MÉTODO: Se estudiaron 21 pacientes con sospecha de EM y un total de 42 brotes. Los pacientes fueron clasificados según los criterios de Lublin y Revingold para las formas evolutivas y según los criterios de McDonald. RESULTADOS: Solo dos pacientes clasificaron en la forma evolutiva progresiva primaria; los primeros dos trimestres del año fueron los de mayor número de brotes. CONCLUSIÓN: Se recomienda profundizar en las variables climatológicas que pudieran tener vínculo con la aparición de estos brotes en nuestro medio.